P12.01 Getting your chlamydia care online: qualitative study among users of the chlamydia online clinical care pathway (chlamydia-occp), in a proof of concept study. (13th September 2015) - Aicken, CRH; Sutcliffe, LJ; Estcourt, CS; Gibbs, J; Tickle, LJ; Sonnenberg, P; Sadiq, ST; Shahmanesh, M
Abstract : Background: Online clinical care was offered to people receiving positive chlamydia results, following testing in Genitourinary Medicine clinics or through six National Chlamydia Screening Programme areas' online postal self-sampling service: 21.07.14–13.3.15, in a proof-of-concept study within the eSTI 2 consortium (www.esti2.org.uk ). Chlamydia-OCCP included: STI results service; clinical consultation; electronic prescription via community pharmacy; partner notification; and a telephone helpline to support patients and to fast-track those with complex needs to clinic. We describe views and experiences of people who chose Chlamydia-OCCP for treatment. Methods: An interviewer conducted 40 in-depth follow-up telephone interviews with a purposive sample. Thematic analysis. Results: Participants described choosing Chlamydia-OCCP over alternatives for its expected greater speed, convenience and privacy; or trying it out without preconceptions. They valued rapid access to treatment, but also obtaining treatment when convenient. Despite general concerns about keeping their chlamydia diagnoses secret, several accessed the online consultation immediately, at work/in public. Participants described Chlamydia-OCCP web-app as easy to use, with only minor technical or privacy issues. They found providing personal/sensitive information online acceptable, reasoning that: 1. it was preferable to (potentially embarrassing) face-to-face consultations; 2. Chlamydia-OCCP was associated with trusted services; 3. they already provided personal information online for other services. Barriers to rapid treatment via Chlamydia-OCCP included: difficulties accessing pharmacy due to employment/carer demands or holiday/business travel (these also impeded clinic access); pharmacy staff's knowledge of process. Collecting treatment from pharmacies was universally acceptable, despite difficulties experienced by some. Reactions of participants fast-tracked to clinic varied (anxiety, disappointment, relief), and helpline contact reassured them, aiding their understanding of why a clinic visit was necessary. Conclusion: Participants expressed satisfaction with the web-app and helpline, using Chlamydia-OCCP to obtain treatment discreetly, conveniently and quickly, despite busy lifestyles. Further evaluation of the pharmacy process will explore how this can be optimised, to further improve time-to-treatment and satisfaction. Disclosure of interest statement: Nothing to declare.